Dengue in the South-eastern region of Brazil: historical analysis and epidemiology - José Carlos Serufo; Andréa Marcia Souza; Valéria Aparecida Tavares; Marcos Cézar Jammal; Josimar Gerônimo Silva
The aim of the study is an historical analysis of the work undertaken by the Public Health organizations dedicated to the combat of the Aedes aegypti, as well as an epidemiolocal study of persons with unexplained fever, with a view to evaluating the ocurrence of dengue within the population. The Mac-Elisa, Gac-Elisa, hemaglutination inhibition, isolation and typage tests were used. Organophosphate intoxication in agricultural workers was also assessed by measuring concentrations of serie cholinesterase. A sera samples of 2,094 were collected in 23 towns, and the type 1 dengue virus was detected in 17 towns and autochthony was confirmed in 12 of them. The cholinesterase was measured in 2,391 sera samples of which 53 cases had abnormal levels. Poisoning was confirmed in 3 cases. Results reveal an epidemic the gravity of which was not officially know. The relationshipe between levels of IgM and IgG antibodies indicates the outbreak tendency. The widespread distribution of the vector is troubling because of the possibility of the urbanization of wild yellow fever, whereas the absence of A. aegypti in 2 towns with autochthony suggests the existence of another vector. Since there is no vaccine against dengue, the combat of the vector is the most efficient measure for preventing outbreaks. The eradication of the vector depends on government decisions which depend, for their execution, on the organization of the Health System and the propagation of information concerning the prevention of the disease using all possible means because short and long term results depend on the education and the active participation of the entire population.